Strategies for Strengthening Digital Leadership in an Effort to Improve the Performance of Higher Education - Mubarok, Ade; Sudirman, Iman; Setiawan, Heru (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
The ability of higher education institutions to utilize digital technologies is increasingly important in responding to the demands of the Fourth Industrial Revolution. Universities are now expected not only to adapt to rapid technological shifts but also to innovate so that learning remains aligned with the evolving needs of the workforce. The degree to which technology is used to strengthen educational services, support strategic goals, and improve operational efficiency significantly affects overall institutional performance. Because of this, universities require a clear and sustainable digital strategy, as strong digital leadership can accelerate transformation and enhance institutional competitiveness. This study adopts a qualitative approach, beginning with identifying the research focus and selecting informants who possess relevant knowledge of the issues examined. Data were collected through interviews and documentation, then analyzed systematically and continuously to identify emerging themes. The credibility of the findings was strengthened using triangulation, which involved comparing data from different sources, methods, and times. The results show that digital leadership practices in both institutions are still in the developmental stage and not yet fully optimized. To strengthen digital leadership, this study recommends integrating transformational leadership principles, encouraging disruptive innovation, improving digital literacy, and establishing a Digital Transformation Office supported by internal policies that promote wider technology adoption.